MENGANGKAT ATRAKTOR BUDAYA DAN KOMUNITAS DI KAWASAN GLODOK UNTUK WADAH EKSPLORATIF KESENIAN DAN EDUKASI GENERASI MUDA - Yordy Christian; Petrus Rudi Kasimun (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
In looking at the developments that have occurred in the Glodok area until now there has been a degradation of Chinese culture which was caused by several aspects of the past, and cannot be separated from the role of the younger generation. Looking at what is there now, with the persistence of Chinese culture, one can see that empathy will be included in terms of cultural values that are passed on to the younger generation and become learning for all levels of society who are interested in more modernism as a form of renewal value. The role of architecture is needed in empathizing with the degraded Chinese culture in the Glodok Chinatown area. The method used to research the issues raised is a mixture of qualitative and quantitative cultural essence values which can later be contained as substance values in buildings and empathy for culture to be preserved. The empathy that is felt from the cultural degradation in the area will later be aimed at cultural actors, parents and the current generation who find it difficult to see the value of Chinese culture in Jakarta. The search is based on the early development of Chinese history in Jakarta. The selected site can respond to the issues raised regarding the degradation of Chinese culture and the problems that occur within the Glodok environment so that the site can have empathetic value conveyed in designing the building. The resulting spatial program responds to issues of cultural degradation that occur, recognition and preservation of culture as things to be emphatic. Keywords:  Chinese; culture; degradation; empathy; Glodok Abstrak Dalam melihat perkembangan yang terjadi di Kawasan Glodok hingga kini terjadi degradasi budaya Tionghoa yang diakibatkan beberapa aspek masa lampau, dan tidak terlepas juga dari peran generasi muda. Melihat apa yang ada sekarang dengan masih adanya ketahanan kebudayaan Tionghoa dapat dilihat empati akan masuk dalam hal nilai kebudayaan yang diwariskan ke generasi muda dan manjadi pembelajaran untuk semua lapisan masyarakat yang tertarik dalam lingkup hal yang lebih modernisme sebagai bentuk nilai pembaharuannya. Peran arsitektur dibutuhkan dalam berempati terhadap budaya Tionghoa yang terdegradasi di kawasan pecinan Glodok. Metode yang digunakan untuk meneliti perihal isu yang diangkat ialah campuran yakni kualitatif dan kuantitatif Nilai esensi kebudayaan yang nantinya dapat tertuang sebagai nilai substansi dalam bangunan dan empati terhadap budaya untuk dilestarikan. Empati yang dirasakan dari adanya degradasi budaya pada kawasan tersebut nantinya ditujukan kepada pelaku kebudayaan, orang tua dan generasi kini yang sulit melihat nilai budaya Tionghoa di Jakarta. Pencarian didasari perkembangan awal mula sejarah Tionghoa di Jakarta. Tapak yang dipilih dapat merespon mengenai isu yang diangkat tentang degradasi budaya Tionghoa dan permasalahan yang terjadi dalam lingkup Glodok sehingga tapak dapat mempunyai nilai empati yang disampaikan dalam mendesain bangunan. Program ruang yang dihasilkan merespon isu tentang degradasi budaya yang terjadi, pengenalan dan pelestarian budaya sebagai hal untuk diempatikan.